Community Based Tourism Development in Belitung Regency Bangka Belitung Island Province - Arnapis Jambak (Faculty of Social Science, Universitas Negeri Padang, 2017)
The purpose of this research was to identify readiness and ways to increase community prosperity in Belitung Regency through the concept of society based tourism development. By the tourism product offered, thus the most appropriate way was promoting the original characters of Belitung Regency community in tourism product development strategy and then developing the development framework, so that tourism activities in Belitung Regency can be a form of sustainable tourism. In order to support the objective, improving the quality of community should be a major concern, so that the community would be able to create tourism products that have competitive and comparative qualities in international market and able to improve and facilitate community potential and tourism potential in Belitung regency to improve the community prosperity which has been relying on the income from mining sector.